The moderating effect of subjective norms on the relationship between peer influence and intention to pay zakat - Muhammad, Sani Adamu; Saad, Ram Al Jaffri (Iosrjournals.org, 2016)
Zakat is among the pillars of Islam which aims at poverty reduction among Muslim Ummah.Zakat is vital for improvement of Asnaf purchasing power. However, the payment of zakat in Kano Nigeria is still low.Despite numerous factors that influence intention to pay zakat recommended in the literature, research model that address this issue is still not enough to solve the problem of low level of zakat payment in developing nations.The core objective of this paper is to suggest a research model for examining the moderating effect of subjective norm on the relationship between peer influence and intention to pay zakat among businessmen in Kano Nigeria.The paper suggests a model which if authenticated empirically will be used by Kano state Zakat and Hubsi commission for policy decision making. Additionally, the paper presents a new variable in zakat environment.